Effects of Lactiplantibacillus plantarum and Lactiplantibacillus brevis on fermentation, aerobic stability, and the bacterial community of paper mulberry silage - Zhang, Yulin; Yang, Hanjun; Huang, Rongzheng; Wang, Xuzhe; Ma, Chunhui; Zhang, Fanfan (Frontiers in Microbiology, 2022)
Lactic acid bacteria (LAB) inoculants are applied to various high protein forages, such as alfalfa and ryegrass, during ensiling to reduce silage nutrient loss. However, few inoculants are applied to paper mulberry (Broussonetia papyrifera) silage. Therefore, the present study investigated the dynamic profiles of fermentation quality, aerobic stability, and the bacterial community of paper mulberry silage inoculants without (Control) or with Lactobacillus plantarum (LP), Lactobacillus brevis (LB), or their combination (LPLB), which was screened from naturally fermented paper mulberry. The results showed that the inoculated treatments had significantly reduced neutral detergent fiber, water-soluble carbohydrates, and ammoniacal nitrogen contents compared with the control after 60 days of ensiling (the decreased proportion of LP, LB, and LPLB ranged from 7.33–11.23%, 9.60–21.44%, and 21.53–29.23%, respectively, P < 0.05). The pH of the LP and LB treatments was significantly lower than that of the control after 60 days of ensiling (4.42 and 4.56 vs. 4.71, P < 0.05). The LP treatment promoted lactic acid accumulation and LAB number compared with the control (66.59% vs. 54.12% and 8.71 log CFU/g vs. 8.52 log CFU/g, respectively, P < 0.05), and the LB and LPLB treatments inhibited the growth of yeast and mold after 14 days of fermentation. After 5 days of aerobic exposure, both the LB and LPLB treatments increased the aerobic stability time and acetic acid content (from 29–75 h and 16.14–48.72%, respectively, P < 0.05), inhibited the growth of yeast and mold, and did not detect butyric acid. Additionally, the bacteria community of each treatment was dominated by Aerococcus on day 3 of ensilage (accounting for 54.36–69.31%), while the inoculated treatments reduced the abundance of Aerococcus on day 60 (from 59.73–85.16%, P < 0.05), and Lactobacillus became the dominant genus (accounting for 54.57–70.89%). Inoculation of L. plantarum effectively maintained the acidic environment at the end of the fermentation system by maintaining the abundance of Lactobacillus, maximizing the preservation of dry matter and protein, and reducing protein corruption. Inoculation of L. brevis alone or in combination with L. plantarum significantly inhibited the growth of mold and improved the aerobic stability of paper mulberry silage.